Visual results of combined cyclosporine-A and bromocriptine treatment in ocular Behçet s disease - Hepsen, I.Feyzi; Erkilic, Kuddusi; Ekinciler, O.Faruk; Mirza, G.Ertugrul; Dogan, Hakki (Annals of Medical Research, 2021)
None
Keywords: Behçet's disease, cyclos/mrine-A, bromocriptine